Expedient synthesis of conjugated triynes via alkyne metathesis. Issue 19 (4th May 2020) - Curbet, Idriss; Colombel-Rouen, Sophie; Manguin, Romane; Clermont, Anthony; Quelhas, Alexandre; Müller, Daniel S.; Roisnel, Thierry; Baslé, Olivier; Trolez, Yann; Mauduit, Marc
Abstract : The first synthesis of symmetrical and dissymmetrical conjugated triynes by self- and cross-metathesis was successfully achieved thanks to the use of hindered diynes. Abstract : The first synthesis of conjugated triynes by molybdenum-catalysed alkyne metathesis is reported. Strategic to the success of this approach is the utilization of sterically-hindered diynes that allowed for the site-selective alkyne metathesis to produce the desired conjugated triyne products. The steric hindrance of the alkyne moiety was found to be crucial in preventing the formation of diyne byproducts. This novel synthetic strategy was amenable to self- and cross-metathesis providing straightforward access to the corresponding symmetrical and dissymmetrical triynes with high selectivity.